Overcoming disparities in transport infrastructure in the reunited Germany between 1990 and 1999 - Eckey, Hans-Friedrich; Horn, Klaus (Raumforschung und Raumordnung | Spatial Research and Planning, 2000)
The quality of transport infrastructure has a major impact on the economic development of regions. Where it is inadequate — as it was in the former GDR at the time of reunification — it can act as a factor stifling growth. For politics, the goal therefore was at that time — and still remains — to improve on the situation found. This article attempts to provide an appraisal of the success to date of attempts to bring about this improvement. As far as rail transport is concerned, counties in the “newLänder” (of the former East Germany) now on average have better connections to the network than counties in western Germany. However, disparities between urban and rural areas have increased considerably. By contrast, relatively little progress has been made so far in up-grading and adding to the road network.
Keywords: Article